Evaluation of the OntoSoft Ontology for describing metadata for legacy hydrologic modeling software. (June 2017) - Essawy, Bakinam T.; Goodall, Jonathan L.; Xu, Hao; Gil, Yolanda
Abstract: Metadata for hydrologic models is rarely organized in machine-readable forms. This lack of formal metadata is important because it limits the ability to catalog, identify, attribute, and understand unique model software; ultimately, it hinders the ability to reproduce past computational studies. Researchers have recently proposed an ontology for scientific software metadata called OntoSoft for addressing this problem. The objective of this research is to evaluate OntoSoft for organizing the metadata associated with a data pre-processing software workflow used in association with the Variable Infiltration Capacity (VIC) hydrologic model. This is accomplished by exploring what metadata are available from online resources and how this metadata aligns with the OntoSoft Ontology. The results suggest that past efforts to document this software resulted in capturing key model metadata in unstructured files that could be formalized into a machine-readable form using the OntoSoft Ontology. Highlights: The OntoSoft Ontology and Portal are evaluated for capturing and sharing metadata for hydrologic modeling software. Data pre-processing software workflow for the Variable Infiltration Capacity (VIC) hydrologic model is used as a case study. 90% of required OntoSoft metadata was obtained for 13 of the 15 software resources. Metadata divided across six sources can now be organized in a constant, machine-readable form.